Genetic bases of compact forms among cucurbit crops - A. V. Inozemtseva; A. G. Elatskova; E. K. Khlestkina; N. A. Shvachko (Труды по прикладной ботанике, генетике и селекции, 2024)
The genetic base of compactness has been an area of active research in recent years, with several genes and mutations identified to be associated with the appearance of dwarf phenotypes. Understanding the functions of these genes and the underlying mechanisms of dwarfism in cucurbit crops is essential for developing new cultivars with improved yield and fruit quality. This study presents current data on genes and mutations associated with the evolvement of compact phenotypes in cucurbit crops. The review includes examples of mutant compact phenotypes and their associated genes in representatives of the Cucurbitaceae family, such as Cucurbita maxima Duch., Cucurbita pepo L., Cucurbita moschata Duch., Citrullus lanatus (Thunb.) Matsum. & Nakai, and Cucumis melo L. The review provides up-to-date information on the genetic and molecular bases of compact phenotype formation, as well as molecular markers for detecting known genes associated with reduced plant size.